Are sukuk debt or equity? A classification of sukuk by regulatory bodies and credit rating agencies / Rafisah Mat Radzi and Nurul Aini Muhamed. - Mat Radzi, Rafisah; Muhamed, Nurul Aini (Universiti Teknologi Mara Selangor, 2019)
Sukuk (Islamic bonds) are the Shariah (Islamic law) instrument that serves as an alternative to conventional bonds that are used in the modern capital market. In theory, sukuk represent a form of equity as they represent certificates conferring ownership to holders of an asset or pool of assets or claim to its cash flows. In practice, they have become known as Islamic bonds with their investors holding debt. Following the question of whether sukuk are debt or equity, this paper aims to classify sukuk from the perspective of regulatory bodies and credit rating agencies. Furthermore, to what extent the innovations in this Islamic instrument make it differ substantially from conventional bonds in practice will be examined.